2016
DOI: 10.1037/xhp0000214
|View full text |Cite
|
Sign up to set email alerts
|

The problem of latent attentional capture: Easy visual search conceals capture by task-irrelevant abrupt onsets.

Abstract: Researchers are sharply divided regarding whether irrelevant abrupt onsets capture spatial attention. Numerous studies report that they do and a roughly equal number report that they do not. This puzzle has inspired numerous attempts at reconciliation, none gaining general acceptance. We propose that abrupt onsets routinely capture attention, but the size of observed capture effects depends critically on how long attention dwells on distractor items which, in turn, depends critically on search difficulty. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
189
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(230 citation statements)
references
References 52 publications
29
189
5
Order By: Relevance
“…At attended locations, participants were slower on invalid trials (531 ms) than valid trials (511 ms), t (35) = 5.196, p < .001, 95% CI [12.3, 28.1], indicating a 20-ms cue validity effect. This finding is consistent with previous studies showing attentional capture by onsets (e.g., Gaspelin et al, 2016) and demonstrates the general sensitivity of our paradigm to detect attentional capture effects.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…At attended locations, participants were slower on invalid trials (531 ms) than valid trials (511 ms), t (35) = 5.196, p < .001, 95% CI [12.3, 28.1], indicating a 20-ms cue validity effect. This finding is consistent with previous studies showing attentional capture by onsets (e.g., Gaspelin et al, 2016) and demonstrates the general sensitivity of our paradigm to detect attentional capture effects.…”
Section: Resultssupporting
confidence: 93%
“…Specifically, we used a somewhat more difficult search task: looking for the target circle and rejecting the oval distractor. Previous research has shown that increasing search difficulty increases cue validity effects from abrupt onsets (Gaspelin et al, 2016, Experiment 7). An added benefit would be demonstrating that the findings of Experiment 1 generalize to a different search task.…”
Section: Methodsmentioning
confidence: 78%
See 2 more Smart Citations
“…There was no time at which oculomotor capture was observed. In summary, although dwell times may sometimes play an important role in the size of observed capture effects (Fukuda & Vogel, 2011; Gaspelin et al, 2016; Geng & Diquattro, 2010; Theeuwes, 2010; van Zoest et al, 2004), the current suppression effects cannot be attributed to mere rapid disengagement.…”
Section: Discussionmentioning
confidence: 83%